An unusual case of severe primary molar infraocclusion - Gondim, Juliana Oliveira; Moreira Neto, José Jeová Siebra; Carvalho, Fernanda Matias de; Costa, Rachel Campelo Ferreira da; Monteiro, Aline Levi Baratta; Giro, Elisa Maria Aparecida [UNESP] (My University, 2013)
Dentoalveolar ankylosis is described as the direct union between root cementum/dentin and alveolar bone. Its etiology is unknown, and conflicting opinions have been presented to explain it. Late detection of ankylosed primary teeth may cause serious problems to the occlusion and generally demands a more complex treatment approach. The purpose of this report is to present an unusual case of severe infraocclusion of the primary maxillary right second molar associated with a posterior crossbite in a 6-year-old child. The initial treatment option was tooth extraction, but the tooth resumed eruption spontaneously. After correction of the posterior crossbite and a 1-year follow-up, the tooth remained in occlusion and the permanent successor was developing without problems. From this unusual outcome, it may be concluded that further investigation of this anomaly of eruption is needed. (J Dent Child 2013;80(2):88-91)
Keywords: Primary teeth; Tooth ankylosis; Tooth extraction; Tooth resorption